THE INFLUENCE OF EMOTIONAL INTELLIGENCE ON EMPLOYEE PERFORMANCE IN SUKADANA CLASS IIB PRISON - Arsyad, Muhamad; Wibowo, Padmono (Journal of Management Small and Medium Enterprises (SMEs), 2025)
This article discusses the influence of emotional intelligence on employee performance at the Class IIB Sukadana Prison. This research measures emotional intelligence through several dimensions, such as the ability to assess one's own emotions, understand other people's emotions, regulate emotions, and utilize emotions. The research results show that there is a significant positive relationship between emotional intelligence and work performance. To maintain high performance and competitive advantage, it is important to develop and improve emotional intelligence systematically and consistently. With a high level of emotional intelligence, employee performance will increase. Keywords: Emotional Intelligence; Employee Performance; Prison